Crozetia Davies (Diptera: Simuliidae): redescription of Cr. crozetensis, Cr. seguyi, number of larval instars, phylogenetic relationships and historical biogeography - Craig, Douglas A.; Currie, Douglas C.; Vernon, Philippe (Zootaxa, 2003)
The taxonomy of the genus Crozetia Davies (Diptera: Simuliidae) is reviewed. Apart from the eggs, all stages of Crozetia crozetensis (Womersley) and Cr. seguyi Beaucournu-Saguez and Vernon, are fully redescribed with only claws and genitalia detailed for the female of Cr. crozetensis. A phylogenetic analysis of the Simuliidae indicates that Crozetia is the sister group of all other members of the extant Simuliini, in agreement with current molecular evidence. Palaeogeological evidence on the age of the Crozet Islands is equivocal, but a very late Cretaceous to early Eocene age (79-54 Mya) is most likely, hence the presence of simuliids on this archipelago is not the result of vicariance from Gondwanaland. Method of dispersal to the Crozet Archipelago may have been via wind or possibly vectored by birds from Africa, as suggested by presence of a basal tooth on the adult female claw. Morphometric analysis of larvae of Cr. seguyi indicates seven instars which is typical for the Simuliidae.